Robert B. Parker's revelation [large type] - Parker, Robert B., 1932-2010 (Wheeler Publishing Large Print, 2017)
"Itinerant lawmen Virgil Cole and Everett Hitch return to confront an escaped criminal in the grittiest entry yet of the New York Times bestselling series. Territorial marshals Virgil Cole and Everett Hitch figured things had finally settled down in Appaloosa when Boston Bill Black's murder charge was dropped. But all that changed when Augustus Noble Driggs was transferred to a stateside penitentiary just across the border from Mexico. Square-jawed, handsome, and built like a muscled thoroughbred stallion, Driggs manages to intimidate everyone inside the prison walls, including the upstart young warden. In a haunting twist of fate, Driggs and a pack of cold-blooded convicts are suddenly on the loose--and it's up to any and all territorial lawmen, including Cole and Hitch, to capture the fugitives and rescue the woman kidnapped during their escape. But nothing is ever quite what it seems with the ever-elusive Driggs. Finally free, he's quickly on his own furious hunt for a hidden cache of gold and jewels--and for the men who betrayed him and left him for dead. With an unlikely and unconventional Yankee detective by their side, Cole and Hitch set off on a massive manhunt. As horses' hooves thunder and guns echo deadening reports, Driggs discovers one of the lawmen on his trail is none other than a fellow West Point graduate he'd just as soon see dead. Ruthless and willing to leave a bloody path of destruction in his wake, Driggs seeks vengeance at any cost"--